2020
DOI: 10.3892/mmr.2020.10986
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CLEC3A inhibits osteosarcoma cell proliferation and promotes their chemosensitivity through the AKT1/mTOR/HIF1α signaling pathway

Abstract: osteosarcoma (oS) is a primary malignant tumor that occurs in bone, and mainly affects children and adolescents. c-type lectin domain family 3 member a (clec3a) is a member of the c-type lectin superfamily, which regulates various biological functions of cells. The present study aimed to identify the effects and related mechanisms of clec3a in the proliferation and chemosensitivity of oS cells. The expression of clec3a in oS was analyzed using the Gene Expression Omnibus data profile GSE99671, and its expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…These genes included PTPN21 (28), ST6GALNAC3 (29), FAM13A (30), and CHRNA7 (31), which were correlated with metastasis. These genes were also enriched in the PI3K/Akt, Notch1/Hes1 or Akt1/ mTOR signaling pathways and were reported to be correlated with LNM in breast cancer (32)(33)(34)(35). The NMRK2 gene was identified as an important target for mitochondrial respiration, and mitochondrial respiration is frequently dependent on metastatic cells (36,37).…”
Section: Discussionmentioning
confidence: 98%
“…These genes included PTPN21 (28), ST6GALNAC3 (29), FAM13A (30), and CHRNA7 (31), which were correlated with metastasis. These genes were also enriched in the PI3K/Akt, Notch1/Hes1 or Akt1/ mTOR signaling pathways and were reported to be correlated with LNM in breast cancer (32)(33)(34)(35). The NMRK2 gene was identified as an important target for mitochondrial respiration, and mitochondrial respiration is frequently dependent on metastatic cells (36,37).…”
Section: Discussionmentioning
confidence: 98%
“…Compelling research has revealed that PI3K/AKT/mTOR signalling could participate in promoting the osteosarcoma process by regulating a variety of target genes. 25 The AKT1/mTOR axis might be involved in the disease progression of melanoma and F I G U R E 4 Overexpression of HK2 weakens the inhibitory effect of sh-SPI1 on the proliferation, metastasis and glycolysis of melanoma cells. A375 cells were cotransfected with sh-SPI1 and oe-HK2.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling research has revealed that PI3K/AKT/mTOR signalling could participate in promoting the osteosarcoma process by regulating a variety of target genes 25 . The AKT1/mTOR axis might be involved in the disease progression of melanoma and modulated by minichromosome maintenance protein 7 (MCM7) 26 .…”
Section: Discussionmentioning
confidence: 99%
“…We could prove the suppression of AKT1 by miR-373-3p in ECa cell lines. AKT1 was an oncogene in several cancer diseases including osteosarcoma, pancreatic ductal adenocarcinoma, colorectal cancer, and breast cancer [32][33][34][35] .Recently, lncRNAs have been implicated in the miRNA/AKT1 axis modulation in www.nature.com/scientificreports/ human cancers. For instance, the LINC00324 counteract miR-615-5p and enhance the expression of AKT1 in lung adenocarcinoma 36 .…”
Section: Discussionmentioning
confidence: 99%